ANALISIS STATISTIK DAN HUKUM KELUARGA ISLAM TERHADAP PERMOHONAN DISPENSASI PERNIKAHAN PADA PENGADILAN AGAMA JEMBER TAHUN 2023-2024 - Irsan; Winning Son Ashari; Fathan Jihadul Islam (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2025)
In 2023, the number of child marriages in Jember Regency is the highest number of child marriages in East Java province. This study aims to conduct statistical analysis and Islamic family law on applications for marriage dispensation at the Jember Religious Court in 2023-2024. This study uses a mixed methods research method that combines qualitative and quantitative approaches. The data in this study are 178 decisions of the Jember Religious Court on applications for marriage dispensation at the Jember Religious Court in 2023-2024 and data from various Islamic family law literature. The results of this study indicate that 21.6% of children registered for applications for marriage dispensation have committed adultery, of which 14.8% have become pregnant, then 77.3% of applications for marriage dispensation were submitted on the grounds of avoiding adultery, and 1.1% were due to having had a secret marriage. Second, the analysis of Islamic family law shows that the district, sub-district and village governments are required to educate young men and women in Jember Regency regarding adultery law, the negative impacts of adultery and promiscuity, and education about the ethics of socializing during puberty.